Silvical Characteristics of Duabanga grandiflora Roxb. Ex DC (Sonneratiaceae) - Beniwal, B. S. (Indian Forester, 1987)
Duabanga grandiflora is a fast growing species occurring naturally in Arunachal Pradesh, Andaman Islands, Assam, Manipur, Meghalaya, Mizoram, Nagaland, Sikkim and Tripura. Earlier plantations of this species were raised by direct seed sowing and It was found that pricking out of seedling was difficult. Now, nursery technique has been developed. Seed is very minute, 54000 seeds weigh to a gram Seed is sown in the mother beds from first week of May to first week of September. Germination is 80% under laboratory conditions and 4-6% under nursery conditions. Seed is viable for 10-12 months. Seeds germinate in about 10-12 days and seedlings are ready for pricking out when they are 2-3 cm high (In 60-65 days after germination). The species can be worked on a rotation of 30 to 35 years. By that time the crop will attain a diameter over 50 cm and it has many advantages over other species for less damage by Mikania species, and managing on short rotation. It requires little care and can be grown on poor soils. There are two main pests which cause maximum damage in plantation and nursery. They are Halica sp. and Auletobius consimilis. The former causes damage in nursery and the latter in nursery as well as in plantations.